Aberrated supraventricular tachycardia associated with neonatal fever and COVID-19 infection. Issue 4 (30th April 2021) - Hopkins, Kali A; Webster, Gregory
Abstract : A 9-day-old girl presented during the 2020 SARS-CoV-2 pandemic in wide-complex tachycardia with acute, symptomatic COVID-19 infection. Because the potential cardiac complications of COVID-19 were unknown at the time of her presentation, we chose to avoid the potential risks of haemodynamic collapse associated with afterload reduction from adenosine. Instead, a transoesophageal pacing catheter was placed. Supraventricular tachycardia (SVT) with an aberrated QRS morphology was diagnosed and the catheter was used to pace-terminate tachycardia. This presentation illustrates that the haemodynamic consequences of a concurrent infection with largely unknown neonatal sequelae present a potentially high-risk situation for pharmacologic conversion. Oesophageal cannulation can be used to diagnose and terminate infantile SVT.